Language, narration and culture of life: the immanent reality of the human in the phenomenology of Michel Henry (2020)
Based on the concepts of  “culture” and  “ontological unity of the human” in the phenomenology of life of Michel Henry, it is pointed out in this article the identity between the knowledge of self-affective life and two of the distinctive features of living human: the word and the narration. Approached from a language of life prior to any linguistic and narrative configuration, the exposure to words is not inscribed in the appearance of the world designated by them but in the original reality of feeling immanent in life in them. Although all language comes from the power and desire of the subjective life to experience itself in every gesture of the body, daily speech and literary creation increase in a particularly intense way this capacity and said desire. Indeed, far from representing life, the “narration of the pathos” realizes the immediate figuration of affect and force. Thus, this work aims to show the novelty of the Henrian theory of the languages of affect regarding, on the one hand, the debate around humanism and post-humanism and, on the other hand, the link between phenomenology and hermeneutics.